Draft Opioid-Prescribing Guidelines for Uncomplicated Normal Spontaneous Vaginal Birth. Issue 1 (January 2019) - Mills, J. Rebecca; Huizinga, Mary Margaret; Robinson, Scott B.; Lamprecht, Lara; Handler, Arden; Petros, Michael; Davis, Teresa; Chan, Kee
Abstract : Women who experience an uncomplicated vaginal delivery have acute intrapartum pain and variable pain in the immediate postpartum period. Although the Centers for Disease Control and Prevention (CDC) has urged clinicians to improve opioid-prescribing behavior, there are no published clinical practice guidelines for prescribing opioids during labor and delivery and at discharge for patients with uncomplicated normal spontaneous vaginal delivery. To address the knowledge gap regarding guidelines for pain management in this population, we used the national Premiere Health Care Database for deliveries of uncomplicated vaginal births from January 1, 2014, to December 31, 2016, to determine the prevalence of opioid administration. Among the 49, 133 women who met inclusion criteria, 78.2% were administered opioids during hospitalization and 29.8% were administered opioids on the day of discharge. Descriptive statistics were generated to document the characteristics of the patients receiving opioids as well as the characteristics of hospitals administering opioids during inpatient labor and delivery and on discharge. Patient-level variables included age group, marital status, race, ethnicity, payer type, and length of stay. Hospital-level variables included bed size, geographic region, teaching status, and urbanicity status. These data were then presented in an electronic Delphi survey to 14 participants. The survey participants were obstetrician–gynecologists identified by the American College of Obstetricians and Gynecologists as being thought leaders in the obstetrics field and who had also demonstrated an active interest in the opioid epidemic and its effect on women's health. After the panelists viewed the opioid administration data, they were presented with an adapted version of the CDC's guidelines for opioid prescribing for chronic pain management. The eight adapted guidelines were constructed to be more relevant and appropriate for the inpatient normal spontaneous vaginal delivery population. After three rounds of the surveying process, seven of the eight adapted guidelines were endorsed by the survey participants. These seven draft consensus guidelines could now be used as a starting point to develop more broadly endorsed and studied guidelines for appropriately managing pain control for women with uncomplicated spontaneous vaginal birth. Abstract : New draft opioid-prescribing data for U.S. hospitals and draft guidelines were developed for informing opioid prescribing in uncomplicated normal spontaneous vaginal delivery.